The Role of Digital Platforms in Shaping Entrepreneurial Innovation Ecosystems - Yunita Wulansari; Nova Syahrani Arasid; Olivia Qurotulain (ADI Bisnis Digital Interdisiplin Jurnal, 2026)
This abstract is developed based on the background that the rapid growth of digital platforms has fundamentally transformed the way entrepreneurs innovate, collaborate, and create value within entrepreneurial ecosystems, particularly in an era of increasingly pervasive digital transformation. The objective of this study is to analyze the strategic role of digital platforms in shaping, strengthening, and integrating entrepreneurial innovation ecosystems through interactions among business actors, technology, and supporting stakeholders. The method employed in this research is a qualitative approach using a systematic literature review of internationally reputable scholarly articles, complemented by a conceptual analysis of digital platform–based innovation ecosystem models published over the past five years. The results indicate that digital platforms function as key enablers by facilitating knowledge exchange, innovative collaboration, market access, and accelerated business development, while simultaneously fostering more adaptive and sustainable ecosystem dynamics. Furthermore, the findings reveal that the success of entrepreneurial innovation ecosystems is strongly influenced by the level of technology adoption, platform governance mechanisms, and entrepreneurs’ capabilities in strategically leveraging digital features. The conclusion of this study emphasizes that digital platforms serve not merely as business support tools, but as a foundational infrastructure in the development of inclusive, competitive, and globally competitive entrepreneurial innovation ecosystems, with significant implications for academics, practitioners, and policymakers in designing effective digital entrepreneurship development strategies.